Pharmacological inhibition of endocannabinoid degradation modulates the expression of inflammatory mediators in the hypothalamus following an immunological stressor - CONNOR, THOMAS JOSEPH (My University, 2012)
The endocannabinoid system is an important regulator of the nervous, neuroendocrine and immune systems, thus representing a novel therapeutic target for stress-related neuroinflammatory and psychiatric disorders. However, there is a paucity of data relating to the effects of endocannabinoids on neuroinflammatory mediators following an immune stress/challenge in vivo. This study investigated the effects of URB597, a selective inhibitor of fatty acid amine hydrolyase (FAAH), the enzyme that preferentially metabolises anandamide, on lipopolysaccharide (LPS)-induced increases in the expression of immune mediators in the hypothalamus. Systemic administration of URB597 increased the levels of anandamide and the related N -acylethanolamines, N -palmitoyl ethanolamide and N-oleoyl ethanolamide, but not 2-arachidonoyl glycerol, in the hypothalamus and spleen. URB597 attenuated the LPS-induced increase in interleukin (IL)-1? expression while concurrently augmenting the LPS-induced increase in suppressor of cytokine signalling (SOCS)-3 expression. In addition, URB597 tended to enhance and reduce the LPS-induced increase in IL-6 and IL-10 mRNA expression respectively. LPS-induced increases in peripheral cytokine levels or plasma corticosterone were not altered by URB597. The present study provides evidence for a role for FAAH in the regulation of LPS-induced expression of inflammatory mediators in the hypothalamus. Improved understanding of endocannabinoid-mediated regulation of neuroimmune function has fundamental physiological and potential therapeutic significance in the context of stress-related disorders.
PUBLISHED
Keywords: Neuroscience; Immunology; Endocannabinoid; anandamide